Specimen Identification Through Multilocus Species Tree Constructed From Single‐Copy Orthologs (SCOs): A Case Study in Cymbidium Subgenus Jensoa - Zheng‐Shan He; Ji‐Xiong Yang; Jia‐Lin Huang; De‐Zhu Li; Jun‐Bo Yang (Ecology and Evolution, 2025)
ABSTRACT Standard barcodes and ultra‐barcode encounter significant challenges when delimiting and discriminating closely related species characterized by deep coalescence, hybrid speciation, gene flow, or low sequence variation. Single‐copy orthologs (SCOs) have been widely recognized as standardized nuclear markers in metazoan DNA taxonomy, yet their application in plant taxonomy remains unexplored. This study evaluates the efficacy of SCOs for identifying recently diverged species within the Cymbidium subgenus Jensoa, where ultra‐barcodes have previously shown limited resolution. Remarkably, over 90% of the 9094 targeted reference SCOs, inferred from three Cymbidium genomes, were successfully retrieved for all 11 representative species in subg. Jensoa using ALiBaSeq at a minimal 5× depth from whole genome shotgun sequences. The species tree, reconstructed from multiple refined SCO matrices under the coalescent model, effectively distinguished all species and identified mislabeled or misidentified specimens. The comprehensive and refined SCO matrices produced by our pipeline not only enhance phylogenetic analysis but also improve the precision of species diagnosis. Additionally, biparentally inherited SCOs, serving as multi‐locus markers, not only augment the effectiveness of DNA barcoding but also support a transition to multi‐locus, species‐tree‐based specimen assignment strategies.